IPCS‐derived APPswe mutant pericytes produce beta‐amyloid and induce the activation of co‐cultured astrocytes. (December 2021) - Wu, Ying Chieh; Rolova, Taisia; Lehtonen, Šárka; Koistinaho, Jari
Abstract: Background: The amyloid cascade hypothesis has been the most prevalent theory so far to explain the molecular mechanisms underlying the pathogenesis and progression of Alzheimer's disease (AD). In parallel, substantial evidence indicates contribution of cerebrovascular dysfunction to development of AD in the early stage of the disease. Cerebral amyloid angiopathy (CAA) is a cerebrovascular disorder characterized by beta‐amyloid (Ab) accumulation in the walls of small and medium vessels in the brain and meninges. Nearly 90 percent of AD patients show CAA pathology linked to vascular dysfunction, eventually leading to hemorrhage lesions in the brain. Pericytes in the blood‐brain barrier (BBB) are crucial for stabilizing the vasculature structure. Substantial pericyte loss has been reported in AD, which correlates with the BBB breakdown and decline of cognitive functions. However, the exact role of pericytes in the AD‐associated vascular dysfunction and AD progression remain unclear. Method: To investigate whether AD pericytes contribute to BBB impairment, we differentiated pericytes from induced pluripotent stem cell (iPSC) lines generated from two APPswe mutant and two healthy control individuals. These generated pericytes were characterized with qPCR or immunostaining to ensure the expression of classic pericyte markers, such as PDGFRb, a‐SMA, and LAMA2. Then, pericytes were co‐cultured with control iPSC‐derived astrocytes to test the interaction of pericytes with another key cell type in BBB. Result: We found that the GFAP immunoreactivity was increased in those astrocytes co‐cultured with APPswe mutant pericytes, indicating activation of astrocytes. We hypothesized that astrocyte activation is triggered by Aβ deposition. Hence, we collected medium from pericyte monocultures after seven days of cultivation and detected by ELISA approx. 64.8 (±23.5) pg/ml of Aβ42 secreted by APPswe pericytes. In control cultures Aβ42 remained undetectable. Conclusion: These results indicate that APPswe pericytes are capable of producing toxic amounts of Aβ42, which could potentially contribute to CAA and affect other surrounding cell types. This is a novel concept since CAA is believed to be caused primarily by neuron‐derived Aβ42.